2018
DOI: 10.1681/asn.2017070798
|View full text |Cite
|
Sign up to set email alerts
|

HDL in CKD—The Devil Is in the Detail

Abstract: The picture of HDL cholesterol (HDL-C) as the "good" cholesterol has eroded. This is even more surprising because there exists strong evidence that HDL-C is associated with cardiovascular disease (CVD) in the general population as well as in patients with impairment of kidney function and/or progression of CKD. However, drugs that dramatically increase HDL-C have mostly failed to decrease CVD events. Furthermore, genetic studies took the same line, as genetic variants that have a pronounced influence on HDL-C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 162 publications
1
58
1
2
Order By: Relevance
“…Lipid metabolism is complex and involves multiple organs, cells and tissues, including the liver, intestine, plasma, macrophages and vascular endothelium, all of which can be affected by impaired kidney function 19,26 (Figure 1). As fats are hydrophobic and generally insoluble in plasma 26 , they are transported within hydrophilic lipoproteins with surface apolipoproteins [H2] Lipoprotein structure LDL-cholesterol has been a major focus of cardiovascular risk reduction in patients with CKD 16,18,19,22,24,[29][30][31][32] . However, the levels of LDL-cholesterol and total cholestrol are often within normal limits in these patients 19,24,25,[32][33][34][35][36] .…”
Section: [H2] Lipid Metabolismmentioning
confidence: 99%
“…Lipid metabolism is complex and involves multiple organs, cells and tissues, including the liver, intestine, plasma, macrophages and vascular endothelium, all of which can be affected by impaired kidney function 19,26 (Figure 1). As fats are hydrophobic and generally insoluble in plasma 26 , they are transported within hydrophilic lipoproteins with surface apolipoproteins [H2] Lipoprotein structure LDL-cholesterol has been a major focus of cardiovascular risk reduction in patients with CKD 16,18,19,22,24,[29][30][31][32] . However, the levels of LDL-cholesterol and total cholestrol are often within normal limits in these patients 19,24,25,[32][33][34][35][36] .…”
Section: [H2] Lipid Metabolismmentioning
confidence: 99%
“…Simple cholesterol measurement might not allow us to obtain the biologic functions of the specific HDL particles [39, 40]. Therefore, functional studies of each HDL component in the cholesterol efflux capacity and the reverse cholesterol transport, would be needed in the future [43]. …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several European studies failed to demonstrate any relationship between HDL and all-cause or cardiovascular mortality [113,114]. In a large study of >33,000 hemodialysis patients, U-shaped association between HDL concentrations of <30 mg/dL and >60 mg/dL and increased risk for total and CVD mortality was observed [115,116]. The results of the Investigation of Lipid Level Management to Understand its Impact in Atherosclerotic Events (ILLUMINATE) trial assessing the impact of torcetrapib (CETP inhibitor) on clinical outcome indicated that despite the fact that the treatment significantly increased HDL levels, the risk of mortality and morbidity in patients at high risk for coronary events remained unchanged [117].…”
Section: Cardiovascular Risk Related To Modifications Of Hdl Particlementioning
confidence: 96%